(untitled) (Research, Society and Development, 2021)
Objectives: To identify facilitators and barriers to the work carried out by multidisciplinary and interdisciplinary teams to stroke patients in hospitals and to identify the health professionals involved. Method: An integrative review was carried out with the search for bases: Virtual Health Library, CINAHL, Cochrane, Embase, PEDro, ProQuest, PubMed, Scopus and Web of Science. Including primary studies published between 2014 and 2020, in English, Portuguese and Spanish, you have a complete report that will answer the guiding question of the review. Results: Selected primary study forums, whose results show a diversity of work carried out by the teams, due to the high demand for care needed by the population with stroke. There is a wide range of professionals in the teams, with only nurses present in all of them. Barriers and facilitators for or teamwork were identified, related to the specific needs of patients. Collaboration and communication appeared as facilitators. The barriers found were insufficient time and lack of involvement of team members. Conclusions: It is important to understand how the different professionals of the teams work together with stroke patients, as it is so crucial to comprehensively assess the context of their personalities and plan chronic care, in a holistic way.